Influence of coal ash on the characteristics of corn straw pyrolysis products. (December 2020) - Qin, Qianwen; Zhou, Jinsong; Lin, Bowen; Xie, Cong; Zhou, Lingtao
Highlights: The effect of industrial solid waste coal ash on biomass pyrolysis was explored. Different experimental parameters were concerned to investigate the influence. The effect of coal ash was more significant with high heating rate. Coal ash increased the yield of pyrolysis gas at 800 °C, while inhibited gas formation at lower temperature. Abstract: To discern influence of inorganic substances in coal on the co-utilization of coal and biomass, coal ash (CA) was added to biomass for pyrolysis. TG–FTIR and fixed bed reactor were used for pyrolysis of corn straw (CS) with CA. XRF and XRD were used to detect the reactants and products components, respectively. At constant heating rate. CA slightly promoted char and gaseous products formation. In the fixed bed reactor, the effect varied with temperature and CA addition ratio. The char and gas yields were changed due to the Si, Al, and other inorganic substances in CA. CS/CA = 1 had the greatest influence on char. Gas yield were reduced at 500–700 °C, but increased at 800 °C with a small proportion of CA. When CA was 1/10 of CS at 800 °C, the gas yield increased by 9.3%, and CH4, CO, and H2 increased by 26.1%, 8.4%, and 37.7%, respectively.